A Measure of Safety Behaviors for Use with Young People: Subtle Avoidance Measure for Youth. Issue 4 (4th July 2022) - Chapman, Cindy; Rapee, Ronald M.
ABSTRACT: Objective : Safety behaviors have been found to undermine successful exposure in the treatment of anxiety disorders for both adults and children. Although reliable measures of safety behaviors have been developed for use with adults, no such measure has been developed specifically for pediatric populations. In light of this limitation, the current study aimed to develop and validate a measure of the use of safety behaviors suitable for children: The Subtle Avoidance Measure for Youth (SAMY). Methods : Clinical (n = 174) and community (n = 138) young people, aged 7–13 years, provided data. Results : Both exploratory and confirmatory factor analyses supported a three-factor solution of the SAMY, which reflected checking behaviors, behaviors related to image management, and behaviors related to physical protection. The SAMY and its subscales demonstrated strong internal consistency, test-retest reliability, construct validity, and the ability to discriminate between clinical and community participants. Conclusions : Given its solid psychometric properties, the SAMY will prove useful for both research and clinical work with anxious young people.